Zein-lac composite nanoparticles loaded with 7-hydroxycoumarin as well as preparation method and application of zein-lac composite nanoparticles
By using corn alcohol-soluble protein-a molcot composite nanoparticles as a carrier, using micro-current control technology to prepare a composite nanoparticles of 7-hydroxycosamison to solve the problem of poor water solution and stability of 7-hydroxycosamis beanins. Its efficient delivery and stable release in drugs improve biological utilization and efficacy.
Patent Information
- Application Number
- CN202411526177.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-01-24
AI Technical Summary
7-hydroxycoumarin has poor water solubility, chemical or thermal instability and susceptibility to pH, oxygen or salt ions in the body in drug applications, limiting its use in drugs.
Use corn alcohol-soluble protein-a mulch composite nanoparticles as a carrier, and solve 7-hydroxycosaccharide, corn alcohol-soluble protein, and amethystly soluble in ethanol solutions through micro-current control technology, and control the total flow rate and water phase of the fluid and water phase. Organic flow rate ratio, prepares corn melolin-mellow protein-apicidal composite nanoparticles serialized with 7-hydroxycosamis.
The prepared composite nanoparticles have good biocompatibility and biodegradability, controllable particle size, good stability, can achieve stable release in the body, improve the bioavailability and efficacy of 7-hydroxycoumarin, and Reduces toxicity during nanoparticle preparation.
Smart Images

Figure CN119345156A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of drug delivery and biomedical materials, and more specifically, to a zein-lac composite nanoparticle loaded with 7-hydroxycoumarin, and a preparation method and application thereof. Background Art
[0002] Natural and synthetic derivatives of coumarin have attracted much attention due to their potential in the field of anti-tumor therapy. Many studies on coumarin derivatives have shown that coumarin compounds have countless pathways of action as anti-cancer drugs and can effectively treat cancer. One of the coumarin family, 7-hydroxycoumarin (7-HC), was selected as a drug for delivery. However, due to its poor water solubility, chemical or thermal instability, and susceptibility to pH, oxygen or salt ions in the body, it is easy to deteriorate, which seriously limits its application in medicine.
[0003] Currently, many polymer nanoparticles have been designed to effectively encapsulate, preserve and deliver drugs. Proteins that are easily absorbed by organisms and are naturally derived rather than synthetic stand out from the crowd. Zein is one of them, which is mainly soluble in acetone, acetic acid, aqueous alcohol and aqueous alkaline solutions. The hydrophobicity, low digestibility, bioadhesion and good cellular uptake of zein make it an ideal candidate for delivering bioactive molecules. However, zein nanoparticles tend to form aggregates during freeze-drying and cannot be dispersed in water. Low colloidal stability limits the application of zein in carrier systems. In addition, due to its hydrophobicity and protein properties, zein particles may cause immunogenicity in humans, which may limit its use in drug delivery.
[0004] In order to overcome these problems, one solution is to choose another biomaterial to cooperate with zein to form composite nanoparticles. This biomaterial is shellac, which is a natural resin and a hydrophobic pH-sensitive polymer with good film-forming ability, high gloss, and low permeability to gas, acid and water vapor, making it useful for coatings of food and medicine. Because both zein and shellac are hydrophobic and negatively charged, when a certain concentration of shellac is introduced into the zein molecular solution, the hydrophobic interaction and electrostatic repulsion between zein and shellac can prevent the formation of large-sized zein molecular aggregates, thereby improving the stability of nanoparticles, reducing particle size and dispersion, and making the drug delivery effect stronger.
[0005] Microfluidics is a versatile technology used to process or manipulate microfluidics in channel structures with dimensions ranging from tens to hundreds of micrometers. Fluids controlled by microfluidics have unique properties, such as laminar flow and droplets. Utilizing these unique fluid phenomena, the mixing conditions of each solvent can be finely controlled and the installation of nanostructures can be precisely controlled to achieve uniformity in the size distribution of synthesized particles. Composite nanoparticles with smaller and narrower size distributions can be prepared by adjusting the flow parameters of the fluid, such as the total flow rate, the flow rate ratio of different solutions, the concentration, and the characteristic length in the microfluidic channel. Summary of the invention
[0006] The invention provides zein-lac composite nanoparticles loaded with 7-hydroxycoumarin, and a preparation method and application thereof. The prepared composite nanoparticles are spherical and have uniform particle size. The composite nanoparticles have good biocompatibility and biodegradability, and no surfactant and dispersant need to be added during the preparation process, thereby further reducing toxicity.
[0007] In a first aspect, the present invention provides a method for preparing zein-lac composite nanoparticles loaded with 7-hydroxycoumarin, comprising the following steps:
[0008] (1) dissolving shellac, zein and 7-hydroxycoumarin in an ethanol solution, filtering the membrane, and obtaining a 7-hydroxycoumarin-shellac-zein ethanol solution;
[0009] (2) The 7-hydroxycoumarin-shellac-zein ethanol solution in step (1) is used as an organic phase and pure water is used as an aqueous phase. A microfluidic method is used to control the total flow rate of the fluid and the flow rate ratio of the aqueous phase to the organic phase to prepare 7-hydroxycoumarin-loaded zein-shellac composite nanoparticles.
[0010] The preparation method is simple in process, easy to operate, flexible and controllable. With the help of microfluidic equipment, the preparation time is greatly shortened by adjusting different experimental parameters. The particle size of the prepared composite nanoparticles is controllable and the particle size is uniform. The carrier has good biocompatibility and biodegradability, and its stability is good, which is conducive to its stable release in the body. In addition, no surfactant and dispersant need to be added in the preparation process of the nanoparticles, which further reduces the toxicity.
[0011] Preferably, in step (1), the microfluidic method specifically uses a vortex mixer device, which rapidly mixes fluid through two connected chambers at a specific pressure, and the fluid flows tangentially into the second chamber through the inlet of the first chamber. After the fluid forms a spiral annular flow in the first chamber, it flows tangentially out of the first chamber through the outlet of the first chamber. During the flow of the fluid in the first chamber, it first contracts and then expands.
[0012] Preferably, in step (1), the mass ratio of zein to shellac is 1:9-9:1.
[0013] Preferably, in step (1), the mass ratio of zein to shellac is 2-5.
[0014] Preferably, in step (1), the mass ratio of zein to shellac is 1:9.
[0015] Preferably, in step (1), the mass ratio of zein to shellac is 2:3.
[0016] Preferably, in step (2), the concentration of 7-hydroxycoumarin is 0.1-8 mg / mL.
[0017] Preferably, in step (2), the concentration of 7-hydroxycoumarin is 4-8 mg / mL.
[0018] Preferably, in step (3), the total flow rate of the microfluidic method is 4-64 mL / min, and the flow rate ratio of the aqueous phase to the organic phase is 1:1-5:1.
[0019] Preferably, in step (3), the total flow rate of the microfluidic method is 4-64 mL / min, and the flow rate ratio of the aqueous phase to the organic phase is 5:1.
[0020] Preferably, in step (3), the total flow rate of the microfluidic method is 32-64 mL / min, and the flow rate ratio of the aqueous phase to the organic phase is 2:1.
[0021] Preferably, the total flow rate of the microfluidic method is 32 mL / min, and the flow rate ratio of the aqueous phase to the organic phase is 2:1.
[0022] Preferably, in step (3), the storage temperature of the prepared nanoparticles is 2-8°C.
[0023] Preferably, in step (3), the storage temperature of the prepared nanoparticles is 4°C.
[0024] In a second aspect, the present invention provides zein-lac composite nanoparticles loaded with 7-hydroxycoumarin prepared by the preparation method according to any one of claims 1 to 8.
[0025] In a third aspect, the present invention provides an application of zein-lac composite nanoparticles loaded with 7-hydroxycoumarin, and use of zein-lac composite nanoparticles loaded with 7-hydroxycoumarin in the preparation of drugs for treating cancer.
[0026] Preferably, the application process of the 7-hydroxycoumarin-loaded zein-lac composite nanoparticles is as follows: placing the 7-hydroxycoumarin-loaded zein-lac composite nanoparticle solution in a 2 mL centrifuge tube, centrifuging in a high-speed low-temperature centrifuge at 15,000 rpm / min and 4° C. for 1 hour, and obtaining drug-loaded nanoparticles after precipitation.
[0027] In summary, this application has the following beneficial effects:
[0028] 1. The composite nanoparticles prepared in the present invention are spherical, with controllable particle size and uniform particle size. The carrier has good biocompatibility and biodegradability, good stability, which is conducive to its stable release in the body, and no surfactant and dispersant need to be added in the preparation process of the nanoparticles, which further reduces toxicity;
[0029] 2. The present invention overcomes the problem of poor water solubility of 7-hydroxycoumarin. The prepared nanoparticles can be evenly dispersed in water, which improves the bioavailability of 7-hydroxycoumarin, increases the therapeutic effect, and has a good sustained release effect. Compared with naked 7-hydroxycoumarin, nanoparticles are more easily taken up by cells and have a more lasting effect of inhibiting tumor cell growth;
[0030] 3. The preparation method of the present invention has the advantages of simple process, convenient operation and can be continuous.
[0031] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not intended to limit the scope of protection of the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] 1. Figure 1 It is a process flow chart of preparing 7-hydroxycoumarin-loaded zein-lac composite nanoparticles of the present invention;
[0033] 2. Figure 2 This is an optimization comparison diagram of the total flow rate of the parameters of the zein-lac composite nanoparticles prepared by microfluidic control of the present invention;
[0034] 3. Figure 3 This is a comparison diagram of the optimization of the flow rate ratio of parameters for preparing zein-lac composite nanoparticles by microfluidic control of the present invention;
[0035] 4. Figure 4 The particle size and PDI graph of composite nanoparticles prepared by using shellac and zein in different mass ratios of the present invention;
[0036] 5. Figure 5 This is a graph showing the effect of 7-hydroxycoumarin concentration on the particle size and PDI of nanoparticles of the present invention;
[0037] 6. Figure 6is an encapsulation efficiency diagram of zein-lac composite nanoparticles loaded with 7-hydroxycoumarin of the present invention;
[0038] 7. Figure 7 is a diagram of drug loading of zein-lac composite nanoparticles loaded with 7-hydroxycoumarin of the present invention;
[0039] 8. Figure 8 is a stability diagram of the zein-lac composite nanoparticles loaded with 7-hydroxycoumarin of the present invention at 4° C. and pH values of 5.5, 7.0 and 7.4;
[0040] 9. Fig. 9 is a TEM image of the zein-lac composite nanoparticles loaded with 7-hydroxycoumarin of the present invention;
[0041] 10. Fig.10 is a SEM image of the zein-lac composite nanoparticles loaded with 7-hydroxycoumarin of the present invention;
[0042] 11. Fig.11 is a biocompatibility graph of the zein-lac composite nanoparticles of the present invention;
[0043] 12. Fig.12 It is a cytotoxicity graph of the zein-lac composite nanoparticles loaded with 7-hydroxycoumarin of the present invention. DETAILED DESCRIPTION
[0044] The present application is further described in detail below in conjunction with the examples. It is particularly noted that if no specific conditions are specified in the following examples, the experiments are carried out according to conventional conditions or the conditions recommended by the manufacturer. Unless otherwise specified, the raw materials used in the following examples can be obtained from common commercial sources.
[0045] Preparation Example
[0046] Preparation Example 1
[0047] A preparation method of zein-lac composite nanoparticles comprises the following steps:
[0048] (1) Weigh 40 mg of zein and 60 mg of shellac and dissolve them in 10 mL of ethanol. Ultrasonicate for 0.5 h to completely dissolve the materials. Use a 0.22 μm organic filter to remove impurities in the solution and load it into a 20 mL syringe 1.
[0049] (2) Pure water is passed through a water filter membrane (0.22 μm) and loaded into syringe 2. Syringe 1 and syringe 2 are installed in a microfluidic device, and the flow rate ratio of the aqueous phase to the organic phase is controlled to be 2:1.
[0050] (3) The total flow rate was set to 32 mL / min, and the nanoparticles were collected at the outlet and stored at 4 °C.
[0051] Depend on Figure 1 It can be seen that the particle size and PDI of the nanoparticles prepared at different total flow rates are obtained. When the total flow rate is greater than 4 mL / min, the particle size does not change much as the total flow rate increases. The PDI (dispersity index) generally decreases first and then increases. Therefore, when the total flow rate of the aqueous phase and the organic phase is fixed at 32 mL / min, the particle size is appropriate and the PDI is the smallest.
[0052] Preparation Example 2
[0053] A preparation method of zein-lac composite nanoparticles comprises the following steps:
[0054] (1) Weigh 40 mg of zein and 60 mg of shellac and dissolve them in 10 mL of ethanol. Ultrasonicate for 0.5 h to completely dissolve the materials. Use a 0.22 μm organic filter to remove impurities in the solution and load it into a 20 mL syringe 1.
[0055] (2) Pure water is passed through a water filter membrane and loaded into syringe 2. Syringe 1 and syringe 2 are installed in a microfluidic device, and the total flow rate is controlled to be 32 mL / min.
[0056] (3) The flow rate ratio of the aqueous phase to the organic phase was controlled to be 2:1, and the nanoparticles were collected at the outlet and stored at 4 °C.
[0057] like Figure 2 As shown in the figure, as the proportion of the aqueous phase increases, the particle size of the prepared nanoparticles decreases, but its PDI increases. When the flow rate ratio of the aqueous phase to the organic phase is selected as 2:1, the particle size and PDI of the prepared nanoparticles are both small, which is the optimal flow rate ratio condition.
[0058] Preparation Example 3
[0059] A preparation method of zein-lac composite nanoparticles comprises the following steps:
[0060] (1) Weigh 40 mg of zein and 60 mg of shellac and dissolve them in 10 mL of ethanol. Ultrasonicate for 0.5 h to completely dissolve the materials. Use a 0.22 μm organic filter to remove impurities in the solution and load it into a 20 mL syringe 1.
[0061] (2) Pure water is passed through a water filter membrane and loaded into syringe 2. Syringe 1 and syringe 2 are installed in a microfluidic device, and the total flow rate is controlled to be 32 mL / min, and the flow rate ratio of the aqueous phase to the organic phase is controlled to be 2:1.
[0062] (3) Collect the nanoparticles at the outlet and store them at 4°C.
[0063] Figure 3 It can be seen that the particle size and PDI analysis of the composite nanoparticles prepared with different ratios of zein (Zein) and lac (Lac) showed that when the mass ratio of zein and lac was 2:3, the particle size and PDI of the composite nanoparticles were better. Finally, the concentration ratio of zein and lac was determined to be 2:3.
[0064] Biocompatibility testing of zein-lac composite nanoparticles:
[0065] (1) HFF-1 cells were seeded in a 96-well plate at a density of 5000 per well, 100 μL was seeded per well, and cultured for 18-24 h. The supernatant was discarded, and the nanoparticles were diluted to the required concentration of 0-500 μg / mL with DMEM, 200 μL was added to each well, and incubated in a cell culture incubator at 37°C and 5% CO2 for 24 h.
[0066] (2) After the incubation, 10 μL of MTT (5 mg / mL) was added to each well and incubated in a 37°C, 5% CO2 cell culture incubator for 4 h. Finally, the supernatant was discarded, 150 μL of DMSO was added to each well, and the cells were incubated in a constant temperature shaker at 160 rpm and 37°C for 15 min. Finally, the absorbance at 570 nm was measured using an ELISA reader.
[0067] from Fig.10 It can be seen that the cell survival rate after adding zein-lac composite nanoparticles is higher than 95%, indicating that the material has good biosafety.
[0068] Example
[0069] Example 1
[0070] A preparation method of zein-lac composite nanoparticles loaded with 7-hydroxycoumarin comprises the following steps:
[0071] (1) Weigh 40 mg of zein, 60 mg of shellac and 1 mg of 7-hydroxycoumarin and dissolve them in 10 mL of ethanol. Ultrasonicate for 0.5 h to completely dissolve the materials and drugs. Use a 0.22 μm organic filter membrane to remove impurities in the solution and load it into a 20 mL syringe 1.
[0072] (2) Pure water is passed through a water filter membrane and loaded into syringe 2. Syringe 1 and syringe 2 are installed in a microfluidic device, and the total flow rate is controlled to be 32 mL / min, and the flow rate ratio of the aqueous phase to the organic phase is 2:1.
[0073] (3) Start the equipment, collect the nanoparticles at the outlet, and store them at 4°C
[0074] Example 2
[0075] (1) Weigh 40 mg of zein, 60 mg of shellac and 5 mg of 7-hydroxycoumarin and dissolve them in 10 mL of ethanol. Ultrasonicate for 0.5 h to completely dissolve the materials and drugs. Use a 0.22 μm organic filter to remove impurities in the solution and load it into a 20 mL syringe 1.
[0076] (2) Pure water is passed through a water filter membrane and loaded into syringe 2. Syringe 1 and syringe 2 are installed in a microfluidic device, and the total flow rate is controlled to be 32 mL / min, and the flow rate ratio of the aqueous phase to the organic phase is 2:1.
[0077] (3) Start the equipment, collect the nanoparticles at the outlet, and store them at 4°C
[0078] Example 3
[0079] (1) Weigh 40 mg of zein, 60 mg of shellac and 10 mg of 7-hydroxycoumarin and dissolve them in 10 mL of ethanol. Ultrasonicate for 0.5 h to completely dissolve the materials and drugs. Use a 0.22 μm organic filter membrane to remove impurities in the solution and load it into a 20 mL syringe 1.
[0080] (2) Pure water is passed through a water filter membrane and loaded into syringe 2. Syringe 1 and syringe 2 are installed in a microfluidic device, and the total flow rate is controlled to be 32 mL / min, and the flow rate ratio of the aqueous phase to the organic phase is 2:1.
[0081] (3) Start the equipment, collect the nanoparticles at the outlet, and store them at 4°C
[0082] Example 4
[0083] (1) Weigh 40 mg of zein, 60 mg of shellac and 20 mg of 7-hydroxycoumarin and dissolve them in 10 mL of ethanol. Ultrasonicate for 0.5 h to completely dissolve the materials and drugs. Use a 0.22 μm organic filter membrane to remove impurities in the solution and load it into a 20 mL syringe 1.
[0084] (2) Pure water is passed through a water filter membrane and loaded into syringe 2. Syringe 1 and syringe 2 are installed in a microfluidic device, and the total flow rate is controlled to be 32 mL / min, and the flow rate ratio of the aqueous phase to the organic phase is 2:1.
[0085] (3) Start the equipment, collect the nanoparticles at the outlet, and store them at 4°C
[0086] Example 5
[0087] (1) Weigh 40 mg of zein, 60 mg of shellac and 40 mg of 7-hydroxycoumarin and dissolve them in 10 mL of ethanol. Ultrasonicate for 0.5 h to completely dissolve the materials and drugs. Use a 0.22 μm organic filter membrane to remove impurities in the solution and load it into a 20 mL syringe 1.
[0088] (2) Pure water is passed through a water filter membrane and loaded into syringe 2. Syringe 1 and syringe 2 are installed in a microfluidic device, and the total flow rate is controlled to be 32 mL / min, and the flow rate ratio of the aqueous phase to the organic phase is 2:1.
[0089] (3) Start the equipment, collect the nanoparticles at the outlet, and store them at 4°C
[0090] Example 6
[0091] (1) Weigh 40 mg of zein, 60 mg of shellac and 80 mg of 7-hydroxycoumarin and dissolve them in 10 mL of ethanol. Ultrasonicate for 0.5 h to completely dissolve the materials and drugs. Use a 0.22 μm organic filter membrane to remove impurities in the solution and load it into a 20 mL syringe 1.
[0092] (2) Pure water is passed through a water filter membrane and loaded into syringe 2. Syringe 1 and syringe 2 are installed in a microfluidic device, and the total flow rate is controlled to be 32 mL / min, and the flow rate ratio of the aqueous phase to the organic phase is 2:1.
[0093] (3) Start the equipment, collect the nanoparticles at the outlet, and store them at 4°C.
[0094] Example 7
[0095] A zein-lac composite nanoparticle drug loaded with 7-hydroxycoumarin comprises the following steps:
[0096] (1) Weigh 40 mg of zein, 60 mg of shellac and 40 mg of 7-hydroxycoumarin and dissolve them in 10 mL of ethanol. Ultrasonicate for 0.5 h to completely dissolve the materials and drugs. Use a 0.22 μm organic filter to remove impurities in the solution and load it into a 20 mL syringe 1. Pass pure water through a water filter and load it into syringe 2. Install syringe 1 and syringe 2 into a microfluidic device, control the total flow rate to 32 mL / min, and the flow rate ratio of the aqueous phase to the organic phase to be 2:1. Start the device, collect the nanoparticles at the outlet, and store them at 4°C.
[0097] (2) 1.5 mL of the freshly prepared drug-loaded nanoparticle solution was placed in a 2 mL centrifuge tube and centrifuged in a high-speed low-temperature centrifuge at 15,000 rpm / min and 4°C for 1 hour to obtain the precipitate at the bottom, i.e., the drug-loaded nanoparticles.
[0098] Determination of the encapsulation efficiency of zein-lac composite nanoparticles loaded with 7-hydroxycoumarin:
[0099] The precipitate was added with methanol for ultrasonic demulsification, and the volume was made up to 5 mL with methanol. The absorbance value was measured, and the mass m1 of 7-hydroxycoumarin was calculated according to the 7-hydroxycoumarin-methanol standard curve. 1.5 mL of drug-loaded nanoparticle solution was taken from the same sample, and methanol was added for ultrasonic demulsification, and the volume was made up to 5 mL with methanol. The absorbance value was measured, and the mass m2 of 7-hydroxycoumarin was calculated. The encapsulation efficiency of zein-lac composite nanoparticles loaded with 7-hydroxycoumarin was obtained by substituting it into the following formula.
[0100] EE%=(m1 / m2)×100%
[0101] Depend on Figure 5 It can be seen that when the concentration of 7-hydroxycoumarin is 4 mg / mL, the drug encapsulation efficiency is 80%, and the selected 7-hydroxycoumarin loading concentration is 4 mg / mL.
[0102] Determination of drug loading capacity of zein-lac composite nanoparticles loaded with 7-hydroxycoumarin:
[0103] Add methanol to the precipitate for ultrasonic demulsification, make the volume to 5 mL with methanol, measure the absorbance, calculate the mass m1 of 7-hydroxycoumarin according to the 7-hydroxycoumarin-methanol standard curve, put the precipitate in a vacuum drying oven, dry it at 25°C overnight, weigh the precipitate to obtain the mass m3, and substitute it into the following formula.
[0104] DLC%=(m1 / m3)×100%
[0105] Depend on Figure 6 It can be seen that when the concentration of 7-hydroxycoumarin is 4 mg / mL, the drug loading is the largest, reaching 30%. Finally, the concentration of 7-hydroxycoumarin is selected to be 4 mg / mL.
[0106] Example 8
[0107] A stability test of zein-lac composite nanoparticles loaded with 7-hydroxycoumarin comprises the following steps:
[0108] (1) Weigh 40 mg of zein, 60 mg of shellac and 40 mg of 7-hydroxycoumarin and dissolve them in 10 mL of ethanol. Ultrasonicate for 0.5 h to completely dissolve the materials and drugs. Use a 0.22 μm organic filter to remove impurities in the solution and load it into a 20 mL syringe 1. Pass pure water through a water filter and load it into syringe 2. Install syringe 1 and syringe 2 into a microfluidic device, control the total flow rate to 32 mL / min, and the flow rate ratio of the aqueous phase to the organic phase to be 2:1. Start the device, collect the nanoparticles at the outlet, and store them at 4°C.
[0109] (2) A portion of the nanoparticles stored at 4°C was taken out every week and the particle size and PDI were measured.
[0110] Depend on Figure 7 It can be seen that the particle size and PDI did not change much within 5 weeks, indicating that the drug-loaded composite nanoparticles had good stability for at least 5 weeks.
[0111] Transmission electron microscopy (TEM) detection of zein-lac composite nanoparticles loaded with 7-hydroxycoumarin:
[0112] Before TEM detection, the sample needs to be dialyzed in ultrapure water for 24 hours through a dialysis bag (molecular weight cutoff 3.5 kDa) until there is no organic solvent such as ethanol in the dialysis bag, and then freeze-dried. The dialyzed drug-loaded nanoparticles are taken and the micromorphology of the sample is evaluated by microscopy at an accelerating voltage of 120 kV. The sample solution is diluted and deposited on a carbon-coated copper grid for transmission electron microscopy analysis.
[0113] like Figure 8 As shown in the figure, it can be seen that the particle size is round and evenly dispersed.
[0114] Scanning electron microscopy (SEM) detection of zein-lac composite nanoparticles loaded with 7-hydroxycoumarin:
[0115] The dialyzed and freeze-dried nanoparticles were observed using a scanning electron microscope and the particle size was measured using a program.
[0116] like Fig. 9 As shown, the particle size of the zein-lac composite nanoparticles loaded with 7-hydroxycoumarin prepared under the optimal conditions is approximately 100 nm, and the particles are evenly dispersed and have a uniform particle size.
[0117] Cytotoxicity (MTT) assay of zein-lac composite nanoparticles loaded with 7-hydroxycoumarin:
[0118] (1) HepG2 cancer cells were seeded in a 96-well plate at a density of 5000 per well, 100 μL per well, and cultured for 18-24 hours. The supernatant was discarded, and 7-HC@Zein / Lac NPs loaded with 7-hydroxycoumarin were diluted with DMEM according to the concentration of 7-hydroxycoumarin of 10-100 μg / mL, 200 μL was added to each well, and incubated in a cell culture incubator at 37°C and 5% CO2 for 24 hours.
[0119] (2) After the incubation, 10 μL of MTT (5 mg / mL) was added to each well and incubated in a 37°C, 5% CO2 cell culture incubator for 4 hours. Finally, the supernatant was discarded, 150 μL of DMSO was added to each well, and the cells were incubated in a constant temperature shaker at 160 rpm and 37°C for 15 minutes. The absorbance at 570 nm was measured with an enzyme reader.
[0120] Depend on Fig.11 It can be seen that when the drug concentration is 100 μg / mL, the cancer cell mortality rate in the drug-loaded composite nanoparticle group exceeds 50%, indicating that zein-lac composite nanoparticles (7-HC@Zein / Lac NPs) loaded with 7-hydroxycoumarin are lethal to cancer cells and have an anti-cancer effect.
[0121] The above is only an exemplary embodiment of the present disclosure, but the protection scope of the present disclosure is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present disclosure should be included in the protection scope of the present disclosure. Therefore, the protection scope of the present disclosure should be based on the protection scope of the claims.
Claims
1. A method for preparing zein-lac composite nanoparticles loaded with 7-hydroxycoumarin, characterized in that: The following steps are involved: (1) dissolving shellac, zein and 7-hydroxycoumarin in an ethanol solution, filtering the membrane, and obtaining a 7-hydroxycoumarin-shellac-zein ethanol solution; (2) The 7-hydroxycoumarin-shellac-zein ethanol solution in step (1) is used as an organic phase and pure water is used as an aqueous phase. A microfluidic method is used to control the total flow rate of the fluid and the flow rate ratio of the aqueous phase to the organic phase to prepare 7-hydroxycoumarin-loaded zein-shellac composite nanoparticles.
2. The preparation method according to claim 1, characterized in that: In step (1), the mass ratio of zein to shellac is 1:9-9:
1.
3. The preparation method according to claim 1, characterized in that: In step (1), the mass ratio of zein to shellac is 2:
3.
4. The preparation method according to claim 1, characterized in that: In step (1), the concentration of 7-hydroxycoumarin is 0.1-8 mg / mL.
5. The preparation method according to claim 1, characterized in that: In step (1), the concentration of 7-hydroxycoumarin is 4-8 mg / mL.
6. The preparation method according to claim 1, characterized in that: In step (2), the total flow rate of the microfluidic method is 4-64 mL / min, and the flow rate ratio of the aqueous phase to the organic phase is 1:1-5:
1.
7. The preparation method according to claim 1, characterized in that: In step (2), the total flow rate of the microfluidic method is 32-64 mL / min, and the flow rate ratio of the aqueous phase to the organic phase is 2:
1.
8. The preparation method according to claim 1, characterized in that: In step (2), the storage temperature of the prepared nanoparticles is 2-8°C. 9 . Zein-lac composite nanoparticles loaded with 7-hydroxycoumarin prepared by the preparation method according to any one of claims 1 to 8 .
10. An application of zein-lac composite nanoparticles loaded with 7-hydroxycoumarin, characterized in that: Use of the 7-hydroxycoumarin-loaded zein-lac composite nanoparticles according to claim 9 in the preparation of a drug for treating cancer.
Citation Information
Patent Citations
Corn prolamine-shellac-curcumin compound colloidal particles and preparation method thereof
CN106822035A
Zein / arabic gum composite nanoparticle and preparation method thereof
CN110051006A
Preparation method and application of shellac-beta-carotene drug-loaded nanoparticles
CN116473232A
Double-load food-grade Janus particles as well as preparation method and application thereof
CN118845731A
Glabridin-Zein complex nanoparticle, manufacturing method thereof and use thereof
KR101902846B1